Optimalisasi Pengawasan Perizinan dan Perpanjangan Trayek Angkutan Kota (Studi di Kabupaten Banjarnegara) - Krisna Pramesti Putra; Indriati Amarini; Ika Ariani Kartini (Kosmik Hukum, 2019)
Municipal transportation means of transportation are required to have a route permit and are obliged to extend route permits that have expired. The issuance of route permits and extension of route permits is carried out by the Transportation Agency. This research is normative juridical research. The data used is secondary data sourced from books, research reports, scientific journals, and legislation. Interviews were conducted to add secondary data. The results showed that many city transportations have not extended their route permits. The Banjarnegara Regency Transportation Office as a service provider carries out supervision, provides guidance/socialization as well as evaluations and reports. The obstacles faced in the supervision are the lack of operational implementation and the attitude of city transport owners who have not routinely extended route permits. Optimization from the Banjarnegara Regency Transportation Office in the form of increased guidance for vehicle owners, coordination with police agencies in law enforcement against violations of route permits. Evaluation is needed in the form of ease of granting route permits and the apparatus' assertiveness against violators of route permits.Keywords: Supervision, Route Permit, City Transportation